RANCANG BANGUN MESIN PEMBUAT BAHAN ADONAN ROTI TIPE HORIZONTAL BERKAPASITAS 10 KG - Sukanto Sukanto (Universitas Muhammadiyah Metro, 2012)
Modern technology recently was impact technology manufacturing of breads. Many mixer machine available on market, but to get special capacity mixer as 10 kg is difficult. The goals of the research to design and manufactur mixer machine with 10 kg capacity. Experimental metode was applied of this study. The opinions data will be collected by some producer and grocer breads responden. Furthermore the conclusion of this machine people need will be design and manufactur. Running test must be done to know performance machine produced. Finally this research was produced mixer machine with 10 kg capacity with mixer unit by screw sumbu horizontal system and 1 phase electric was applied. Dimension machine is ±85 x 65 x100 cm. Running test was done with good result, breads batter material ductile and kalis suitable to breads. Beside that’s the capacity of mixer was increase until 3 time form 1 – 3 kg